PENGARUH KEBIASAAN BELAJAR, KEMAMPUAN BERPIKIR KRITIS, KETERAMPILAN BERKOMUNIKASI, PENGGUNAAN MEDIA PEMBELAJARAN DAN DUKUNGAN ORANG TUA TERHADAP PRESTASI BELAJAR PELAJARAN EKONOMI - Nova Aulia Putri; jolianis; Nisha Selvia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of study habits, critical thinking skills, communication skills, the use of learning media, and parental support on students’ learning achievement in economics subject for grade X students at SMA Pertiwi 1 Padang. This research employed a quantitative approach with a population of 132 students and a sample of 76 students selected using stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed with multiple linear regression. The findings reveal that partially, study habits, critical thinking, communication skills, learning media, and parental support have a significant positive effect on students’ achievement. Simultaneously, these five variables also significantly influence students’ academic performance. The study concludes that both internal and external factors contribute significantly to students’ learning outcomes. The implication of this research is to provide considerations for teachers, parents, and schools in improving the quality of learning.